Dextrocardia, situs solitus, double–inlet, and double-outlet left ventricle – A case report - Mehrotra, Akhil; Sharma, Ajay; Kacker, Shubham (Indian Journal of Child Health, 2022)
Dextrocardia is embryologic malformation characterized by displacement of the largest axis of the heart to the right side of the chest. Dextrocardia is a rare anomaly that is associated with situs inversus and the incidence in the general population is usually 1:10,000, with situs solitus being 1:30,000 live births. It is associated with complex cardiac lesions, 5% with situs inversus, and 90% with situs solitus color. Doppler echocardiography not only provides additional information but also improves overall specificity of two-dimensional echocardiography. Few case reports of dextrocardia, double-inlet (DILV), and double-outlet left ventricle (DOLV) with situs inversus have been diagnosed and reported by echocardiography, but none are available with situs solitus. To the best of our knowledge, we are presenting the first case report of dextrocardia, situs solitus, double-inlet with DILV, DOLV, and D-malposition of great arteries with pulmonary stenosis, detected by color Doppler echocardiography.